Timetable for closing not yet set (Raton, NM Raton Range, 1993)
Article is about the closing of the Sears store in Raton.
Newspaper article
Master list item #: 66
File location is in the Raton file Cabinet
Keywords: Caylor, Ivan; Sears Catalog Store; Business closings; Local Business; Retail Stores; Timetables; Raton, New Mexico